A novel fragile X syndrome mutation reveals a conserved role for the carboxy‐terminus in FMRP localization and function. Issue 4 (18th February 2015) - Okray, Zeynep; de Esch, Celine EF; Van Esch, Hilde; Devriendt, Koen; Claeys, Annelies; Yan, Jiekun; Verbeeck, Jelle; Froyen, Guy; Willemsen, Rob; de Vrij, Femke MS; Hassan, Bassem A
Abstract Loss of function of the FMR1 gene leads to fragile X syndrome (FXS), the most common form of intellectual disability. The loss of FMR1 function is usually caused by epigenetic silencing of the FMR1 promoter leading to expansion and subsequent methylation of a CGG repeat in the 5′ untranslated region. Very few coding sequence variations have been experimentally characterized and shown to be causal to the disease. Here, we describe a novel FMR1 mutation and reveal an unexpected nuclear export function for the C‐terminus of FMRP. We screened a cohort of patients with typical FXS symptoms who tested negative for CGG repeat expansion in the FMR1 locus. In one patient, we identified a guanine insertion in FMR1 exon 15. This mutation alters the open reading frame creating a short novel C‐terminal sequence, followed by a stop codon. We find that this novel peptide encodes a functional nuclear localization signal (NLS) targeting the patient FMRP to the nucleolus in human cells. We also reveal an evolutionarily conserved nuclear export function associated with the endogenous C‐terminus of FMRP. In vivo analyses in Drosophila demonstrate that a patient‐mimetic mutation alters the localization and function of Dfmrp in neurons, leading to neomorphic neuronal phenotypes.